2016
DOI: 10.1111/boj.12415
|View full text |Cite
|
Sign up to set email alerts
|

Narrow water barriers prevent multiple colonizations and limit gene flow among California Channel Island wild buckwheats (Eriogonum: Polygonaceae)

Abstract: The relative roles of chance colonization and subsequent gene flow in the development of insular endemic biotas have been extensively studied in remote oceanic archipelagos, but are less well characterized on nearshore island systems. The current study investigated patterns of colonization and divergence between and within two wild buckwheat species (Polygonaceae), Eriogonum arborescens and E. giganteum, endemic to the California Channel Islands to determine whether geographical isolation is driving diversific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
2
2
0
Order By: Relevance
“…The repeated emergence of the land bridge between mainland China and Hainan Island provided opportunities for the plant to disperse from mainland China to Hainan Island (Nm = 0.6443-0.6449). The result was consistent with the study of Quercus pacifica [41] and Eriogonum arborescens [43] in California Channel Islands, where historical gene flow attenuated the population differentiation caused by strait isolation. On the contrary, the genetic differentiation would be high if the historical gene flow was very low (Nm = 0.000-0.004), for example, Amentotaxus argotaenia on Taiwan island [44] and Nigella species in eastern Aegean [45].…”
Section: Discussionsupporting
confidence: 91%
“…The repeated emergence of the land bridge between mainland China and Hainan Island provided opportunities for the plant to disperse from mainland China to Hainan Island (Nm = 0.6443-0.6449). The result was consistent with the study of Quercus pacifica [41] and Eriogonum arborescens [43] in California Channel Islands, where historical gene flow attenuated the population differentiation caused by strait isolation. On the contrary, the genetic differentiation would be high if the historical gene flow was very low (Nm = 0.000-0.004), for example, Amentotaxus argotaenia on Taiwan island [44] and Nigella species in eastern Aegean [45].…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of differentiation between the Northern and Southern Channel Islands is consistent with other studies (e.g. Funk et al, 2016; Hofman et al, 2015; Riley et al, 2016) and highlights how the these two geologically distinct groups of islands are largely independent with respect to broad patterns of diversification.…”
Section: Discussionsupporting
confidence: 91%
“…For species that are not known to have been widely used by Native Americans and do not have obvious properties for high mobility, it is more difficult to make inferences about their means of dispersal and gene flow. For the Channel Islands, studies have more often suggested gene flow from north to south (Ramirez and Beckwitt, 1995; Chatzimanolis et al, 2010; Riley et al, 2016). By contrast, our analyses suggest that gene flow in A. dendroideus has occurred from Santa Catalina northward.…”
Section: Discussionmentioning
confidence: 99%